Phenomenology, Psychotherapy and the Quest for Intersubjectivity - Barua, Archana (The Indo-Pacific journal of phenomenology, 2014)
Intersubjectivity is a key concept in phenomenology as well as in psychology and especially in psychotherapy, given the reliance of the therapeutic process on its location in relationship. While psychotherapy encompasses a range of what Owen (2006) terms "talking therapies", this paper focuses mainly on the Freudian model of psychoanalysis and its connection with Husserlian and Heideggerian phenomenology respectively. Freud’s recognition that symptoms have meaning, and that the methodical disclosing of their meaning needs to be guided by the experience of the patient, accords with the emphasis of phenomenology on empathic attunement to the lived experience of the other. Insofar as the orientation of psychoanalysis towards methodically disclosing meaning gives it a hermeneutic dimension, it is also compatible methodologically with the interpretative mode of phenomenology. While Karlsson (2010, p. 13) identifies seven centrally significant "points of connection" between psychoanalysis and phenomenology, Thompson (2005, p. 40) suggests that "psychoanalysis is already phenomenological in its latency … . Indeed, Freud’s principles of technique make little sense outside a phenomenological context".Can it thus be claimed that, in the quest for intersubjectivity, sufficient common ground exists for meaningful dialogue between psychotherapy, psychoanalysis and phenomenology in general, and between Sigmund Freud, Edmund Husserl and Martin Heidegger in particular? That is what this paper seeks to explore.The paper proceeds from pointing to the ambiguity of the Freudian mode as simultaneously natural scientific and hermeneutic to exploring the fundamental points of difference and commonality between psychoanalysis and phenomenology, and in particular the significance of the role of the unconscious and intentionality in psychoanalysis and phenomenology respectively, as well as the orientation of both towards greater understanding of one’s being in the world. Ultimately, however, the authors conclude that, while the points of commonality would seem conducive to dialogue between the Freudian and the phenomenological in the psychotherapeutic domain, their differences in aims and approach, each shaped by a different view of humankind, continue to obstruct it. The quest for it nevertheless remains ongoing, as demonstrated not only by the academic endeavours of theoreticians such as Owen and Karlsson, but by the contemporary urge of second century psychoanalysis for a theoretically coherent turn away from the Cartesian and towards the authentically intersubjectively relational.